APLIKASI PENGOLAHAN DATA PASIEN STUDI KASUS RSUD SAWERIGADING PALOPO SULAWESI SELATAN - Haris, Abdul; Burhan, Alan (PETIR, 2015)
Currently the Hospital Sawerigading Palopo still using manual systems in data processing inpatients and outpatients, the data processing system are now experiencing difficulties in finding the necessary patient data so it takes a long time. In addition the processing of patient data with the current system does not have a good reporting system, so we need a new system, which can overcome these problems. Therefore, Sawerigading Regional General Hospital (Hospital Sawerigading) require patient data processing applications that are capable of handling a variety of obstacles above. Applications will facilitate the processing of patient data to hospital officials in data processing and printing patient reporting of patient data.